PD-014 Adipose Derived Mesechymal Stem Cells Bound to Artificial Matrix for the Treatment of Perianal Fistulas in Crohn's Disease. (February 2017) - Amy, Lightner; Eric, Dozois; Allan, Dietz; Joel, Fletcher; William, Faubion
Abstract : Background: Perianal fistulizing Crohn's disease (CD) remains notoriously difficult to treat despite several available medical and surgical treatment options. Recent investigation has suggested that mesenchymal stem cells (MSCs) and newly available bioabsorbable plugs may each individually improve the treatment efficacy for perianal CD. We developed a novel protocol to deliver MSCs impregnated on a bioabsorbable plug for the treatment of medically and surgically refractory perianal CD. We herein report our 6 month results on the safety and efficacy of this novel therapeutic for perianal CD in the setting of a phase I clinical trial. Methods: Adult patients with refractory single tract perianal CD were identified. Consent was obtained for enrollment into this phase I clinical trial. Fat pad harvest for MSC generation and exam under anesthesia (EUA) with seton placement into the perianal fistula tract was performed as the initial operation. After expansion of MSCs and adherence to the bioabsorbable GORE plug, plugs were surgically placed into the fistula tract at 6 weeks following seton placement. Patients were then followed with a series of physical exams (post-operative day 1, and week 2, 4, 8, 12, and 24) and magnetic resonance imaging (MRI) (preoperative, week 12 and 24) to determine clinical and radiographic healing. Clinical healing was defined by cessation of drainage and radiographic healing was defined by reduction in the Van Aasche score on MRI. Results: Eleven patients (6 female, average age 34 yr) with an average duration of 8 years of perianal CD and average of 6 prior EUAs were included. All had successful MSC expansion and adherence to the fistula plug. Placement of the MSC-coated fistula plug was not associated with any serious perioperative adverse events. At 6 months, 8 of 11 patients (73%) had complete clinical healing as defined by resolution of drainage on exam, and radiographic healing confirmed by a reduction in the Van Aasche score on serial MRI imaging. In the 3 patients without healing: one developed an abscess requiring drainage and seton placement, another developed a second tract off the fistula which required a seton, and the last has minor ongoing drainage at 6 months. Conclusions: Our novel protocol utilizing a MSC-coated fistula plug for the treatment of refractory perianal fistulizing CD is safe and demonstrates clinical and radiographic healing in 73% of the patients at 6 months.